The possibilities of transcribing orchestral works subject to essentiality of their original orchestration - Rytis Urniežius (Musicologica Brunensia, 2017)
The relationship of orchestration with other means of musical expression and its influence upon the possibilities of transcribing musical works are analysed in this article. The criteria of transcribing symphonic music for the wind band are considered. The demand for the quality of transcriptions induces to ground the criteria of transcribing. The role of the original orchestration in a particular piece of music is an especially important criterion. One of the main conditions determining the quality of transcriptions is the adequacy of original orchestration and the orchestration of the transcription. It was deduced that the relationship between orchestration and the rest of the musical material might be immanent, essential or auxiliary, inessential. According to the type of this relationship, a different approach to the transcribing should be applied in every particular case. The comprehensive cognition of original orchestration and pursuing the adequacy of timbres in transcriptions limit the quantity of the compositions suitable for transcribing and determine the possibilities of its interpretation.